Proceso de adaptación de los Inventarios de Desarrollo Comunicativo MacArthur-Bates al castellano estándar del Perú - Blume del Río, María (2019)
We present here the adaptation process of the MacArthur-Bates Communicative Development Inventories (CDI) to the standard Peruvian Spanish and the version of the inventories resulting from this process. These are a tool for the study of early communication (gestures and vocalizations), the initial vocabulary and the first grammatical constructions, for children between 8 and 15 months and children between 16 and 30 months of age. Having a version adapted to Peruvian Spanish will enhance the development of research on early development issues in our country, especially, but not only, linguistic and communicative aspects. In the applied sphere, these inventories are used to detect possible language and developmental disorders. They are, then, indispensable tools, of proven reliability and validity, to measure the communicative development of our children.